THE USE OF AFTER-READING CARD GAME TO IMPROVE STUDENTS’ VOCABULARY - Desi Ratna Sari Manurung; Jim Ronny Tuna; Nihta V. F. Liando (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The aim of the research is to find out the effectiveness of the After-Reading Card Game in improving students’ vocabulary. This research is quantitative research with a pre-experimental design (One Group Pretest and Posttest design). This research is conducted at SMA Negeri 1 Remboken with 25 10th grade students as the subject. Pretest and posttest are used as the instrument to collect the data. The data are analyzed using the SPSS 22(Statistical Product and Service Solutions). The result of the data shows that the pre-test (22.88) is lower than the post-test (52.28). The result of the research leads to the conclusion that Reading Card Game has a significant effect for students’ vocabulary improvement and students more active on learning process. It means that the use of the after-reading card game can give contribution in improving the quality of English language teaching and learning, especially in improving students’ vocabulary.